White women, race matters : the social construction of whiteness - Frankenberg, Ruth (University of Minnesota Press, 1993)
Beginning with the premise that race shapes white women's lives, just as much as gender shapes men's lives or sexuality shapes heterosexual lives, the author examines, through 30 life-history interviews, just how this "whiteness" is constructed. "Whiteness" is not an empty signifier, but rather a multifaceted daily experience of racial structuring, and through ethnographic descriptions of the 30 womens' lives, Frankenberg provides evidence that "whiteness" is a specific set of cultural practices